THE EFFECT OF MIND MAPPING TO STUDENTS’ ABILITY IN READING COMPREHENSION AT THE EIGHTH GRADE STUDENTS OF SMP SWASTA AL-MUKMIN - Siti Aminah Hasibuan (English Education Study Program FKIP Universitas Alwashliyah Medan, 2022)
The students of the eighth grade at SMP Swasta Al-Mukmin had difficulty in understanding the text which caused them could not find the main essence of the text. Thus, this research was conducted to know the effect of mind mapping on students’ ability in reading comprehension. This research was conducted using a quantitative quasi experimental design. The sample was divided into two groups, namely experimental group and control group which consisted of 35 students for each. This research used pre-test and post-test in the form of reading comprehension test as the research instrument. The research result concluded that the students who were taught by mind mapping had a better reading comprehension. The data analysis showed the pre-test mean score of experimental group was 55.4 while the control group was 54.5 and the score was increased after applying mind mapping. The post-test mean score of experimental group was 77.7 and 69.5 for control group. The value of mean score of both groups was calculated using T-test. It was obtained the value of T-count was 3.96 while T-table was 1.66 under the degree of freedom 68 and the degree of significance 5%. Since T-count value was higher than T-table value, the hypotheses were proved. Therefore, it is stated that Ha (alternative hypothesis) was accepted and Ho (null hypothesis) was rejected. Based on this research result, it is suggested that the English teachers apply the mind mapping technique since this technique is one of many ways teachers can apply to enhance students reading comprehension of texts easily and efficiently.